Analisis Pengaruh Pelatihan Dan Pengembangan SDM Terhadap Kinerja Pada Pegawai BPS Kabupaten Ogan Ilir - Juwita, Reni (Jurnal Ilmiah Bina Manajemen, 2019)
This study aims to develop an understanding of training and HR development as a measurement tool in implementing performance in BPS Ogan Ilir Regency. The method used in this research is multiple linear regression analysis. Based on the results of the study, it was found that the training did not significantly influence the performance of BPS Ogan Ilir Regency employees. While HR development has a significant effect on performance in BPS Ogan Ilir Regency employees. And the two training and development variables also jointly affect the performance of BPS Ogan Ilir Regency employees.